Compliance Management in Financial Industries A Model-based Business Process and Reporting Perspective - Eggert, Mathias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Since the peak of the world financial crisis in 2008, compliance management has gained more and more interest from practice and research. In particular the financial service industry is strongly regulated and has to follow specific laws, standards and guidelines. Considering the steadily increasing number of legal requirements in the design of information systems is a challenge to financial service providers. This book investigates the challenges of compliance management in financial industries and provides solutions for a compliant design of information models. From a business process perspective, an approach is presented that enables the automatic checking of business process models. From a supervisory reporting perspective a modeling technique is presented that allows for modeling regulatory data warehouse requirements as well as its analysis. Besides these two perspectives the author provides insights into the perceived relationship of Information Systems and Law.
Introduction -- Research Background -- Compliance Management and Regulatory Requirements -- Regulatory Environment of Banks -- Business Process Modeling -- Business Process Compliance Analysis -- Data Warehouse Development -- Multisensory Law and Legal Visualization -- Regulatory Requirements Engineering -- Research Design -- Design Science Research -- Complementary Research Methods -- Research Process and Outcome -- Research Results -- Compliance Management and Information Systems -- Business Process Compliance -- Reporting Compliance -- Collaboration of IS Experts and Legal Experts -- Discussion and Outlook.
Keywords: Economics; Information systems; Computer science; Auditing; Management information systems; Economics/Management Science; Business Information Systems; Information Systems and Communication Service; Finance/Investment/Banking.; Models and Principles; Accounting/Auditing.